Political legitimacy crisis in Indonesia: the Aceh case - Abdullah Sani Usman, (Penerbit UKM, 2010)
The legitimacy crisis in Aceh had been in existence since the Sultanate era until the post-independent Indonesia. In this phase, the crisis centred around the issue of authority. This research discusses Aceh’s legitimacy crisis since independence until the signing of the Memorandum of Understanding between the government of Indonesia and the Free Aceh Movement (GAM) in Helsinki in 2005. During the era of the old order, the crisis had its origin in the political conflict which had erupted between the Aceh government and the central government of Indonesia after Jakarta decided to forcibly shift and merge the authority of the Aceh province into that of Northern Sumatra. The political turmoil led to the rebellion of the Darul Islam or Tentera Islam Indonesia whose cause was for the implementation of Islamic Shari’a in Aceh. Under the new order government, on the other hand, the emergence of GAM was attributed to its struggle for sovereignty or self-determination. This study reviews Habermas arguments that the cause of legitimacy crisis in capitalist countries was brought about by economic factors. In addition, Habermas also pointed out that historical issues could be the contributing factors for such crises. Using library sources and interviews, this research found that the crisis in Aceh under the old order government was attributed to the political crisis which was based on ideological factors and centred around the demand for the implementation of Islamic Shari`a. However, under the new order government, the cause for the crisis was the insistence for sovereignty or self-determination based on historical factors. The research attempts at debating the views of Habermas as a great theorist of the legitimacy crisis. In discussing a very important issue, it is obvious that he had missed the point that the cause of the legitimacy crisis is political power rather than economic factors.